ANÁLISE MORFOLÓGICA DE NEOLOGISMOS NASVARIEDADES DE GUARANI CHAQUEÑO (CHIRIGUANO)DA BOLÍVIA - Liliana Paredes Moreno (2023)
This study aims to present a morphological description of neological units from three linguistic varieties of Chiriguano Guarani, Ava, Simba and Izoceño, contained in the book “Neologismos Lingüísticos de Términos Técnicos en Idiomas Bésɨro-Mojeño-GuaraniGwarayu”, with the aim of understanding, not only the linguistic structure of these neologisms, but also, as an additional point, to reflect on aspects of language policies and on the maintenance of Indigenous identity in a multilingual context. Methodologically, we analyzed written materials, selecting words and expressions not included in the dictionary, but already accepted by Indigenous institutions and authorities, in addition to the data collected between the years 2017 and 2019 (PAREDES, 2019), during master’s thesis research. For the development of the analysis of these neologisms, we seek to present a brief phonetic description, using resources from the theory of acousticarticulatory analysis (BARBOSA; MADUREIRA, 2015; LADEFOGED, 2000, 2001). Phonological interpretation is based on the principle of natural classes (HYMAN, 1975) and on the theory of distinctive features (JAKOBSON, 1972 [1932], 1972 [1938], 1978). The morphological analysis is inspired by (COSERIU, 1981). The results, although preliminary, point to a mechanism of word formation by composition, predominantly speaking.